Gp85 protein encapsulated by alginate-chitosan composite microspheres induced strong immunogenicity against avian leukosis virus in chicken - Lei, Tianyu; Liu, Rongchang; Zhuang, Liyun; Dai, Tingting; Meng, Qingfu; Zhang, Xiaodong; Bao, Yinli; Huang, Cuiqin; Lin, Weiming; Huang, Yu; Zheng, Xintian (Frontiers in Veterinary Science, 2024)
Avian leukosis, a viral disease that primarily impacts chickens and other birds, poses significant challenges, including tumor formation, reduced egg production, and increased mortality. The lack of a commercial vaccine has resulted in widespread documentation of avian leukosis virus (ALV) infections, leading to substantial economic losses in the poultry industry over the past two decades. This study developed Alginate-Chitosan Composite Microspheres loaded with the ALV-J Gp85 protein (referred to as aCHP-gp85), using sodium alginate and chitosan as the encapsulating materials and the ALV-J Gp85 protein as the active ingredient. A study involving 45 Specific Pathogen-Free (SPF) chickens was conducted to assess the immunological effectiveness of aCHP-gp85 compared to a traditional Freund adjuvant-gp85 vaccine (Freund-gp85) after two vaccination rounds. The results showed that aCHP-gp85 induced a significant and sustained increase in antibody levels (P<0.05) compared to the Freund-gp85 group, with the elevated response lasting for 84 days. Additionally, aCHP-gp85 significantly boosted the mRNA expression levels of crucial immune markers, including IL-6, IL-1, TNF-α, and IFN-γ, especially showing remarkable increases in TNF-α and IFN-γ mRNA levels (P<0.01). Within the aCHP-gp85 group, the application of the ALV-J Gp85 protein led to a significant increase in splenic lymphocyte proliferation and immune response (P<0.05). In an animal challenge experiment, aCHP-gp85 significantly reduced the presence of the ALV-J virus and improved the clinical condition of infected chickens (P<0.01). Notably, neither the aCHP-gp85 group nor the negative control group exhibited significant pathological changes. Additionally, aCHP-gp85 was effective in reducing virus loads in the spleen and kidney (P<0.01) compared to other groups. In summary, the aCHP-gp85 vaccine elicited a strong and prolonged immune response compared to the Freund-gp85 vaccine, highlighting its potential as an innovative ALV-J vaccine candidate. This study offers important academic and practical insights for tackling avian leukosis in the poultry sector.